Alkenes as hydrogen trappers to control the regio-selective ruthenium(ii) catalyzed ortho C–H silylation of amides and anilides. Issue 3 (19th October 2020) - Lin, Qiao; Lin, Zirui; Pan, Mingxing; Zheng, Qiaojin; Li, Hui; Chen, Xiuwen; Darcel, Christophe; Dixneuf, Pierre H.; Li, Bin
Abstract : A convenient and practical pathway to versatile silylated amides and anilides is described via efficient and selective ruthenium(ii ) catalyzed ortho C–H silylation with different alkenes as the hydrogen acceptors. Abstract : A convenient and practical pathway to versatile silylated amides and anilides is described via efficient and selective ruthenium(ii ) catalyzed ortho C–H silylation. Both amides and anilides were successfully silylated with good functional group tolerance and high regioselectivity. Different alkenes as the hydrogen acceptors played a crucial role in these two catalytic systems. Unexpectedly, two pathways for RuHCl(CO)(PPh3 )2 /KOAc catalyzed C–H silylation involving a 5-membered ruthenacycle with arylamides and a 6-membered ruthenacycle with arylanilides, take place depending on the nature of the alkene as the hydrogen trapper.